Ultrasound Pitfalls in a Complex Fetal Cardiac Malformation—Case Report of a New Arteriovenous Central Communication - Roxana Elena Bohîlțea; Adrian Dumitru; Radu Vlădăreanu; Liana Pleș; Tiberiu Augustin Georgescu; Ioan-Andrei Petrescu; Octavian Munteanu (Diagnostics, 2021)
Cardiac and cardiovascular malformations are of real interest in terms of definition, epidemiology, and means of early diagnosis by imaging. Although ultrasound examination reaches exceptional performance nowadays, unusual pathologies are still exposed to the risk of either incorrect acquired image or misinterpretation by the specialist in a routine scan. Herein, we present a case of a 20-week-old fetus (from an apparently low-risk pregnancy) with complex cardiac and vascular abnormalities, including an arteriovenous malformation along with ventricular septal defect, ductal coarctation of the aorta, aneurysm of a brachiocephalic vein, and dilation of the entire neck and upper mediastinum venous system, and the limitations that were encountered in the process of diagnosis and management of the case.